Towards Sustainable Farming: An Analysis And Review Of The European Union’s Agricultural Subsidy Policy - De Deyne, Laura (Journal of Sustainable Development Law and Policy, 2025)
This paper provides an overview of the most important European agricultural subsidies,which aim at promoting a more sustainable way of farming. The European Union has putthese subsidies into place in order to create a better balance between agriculture and theenvironment. Through these ‘green’ subsidies agro-biodiversity can be protected, which is avery important goal since approximately 50% of all species in Europe depend on agriculturalhabitats or landscapes. The major pressures on biodiversity in agricultural land result fromchanges in the type and intensity of farming, which generate changes in agriculturallandscapes. Such changes can result either from intensification or abandonment, both of whichcan be detrimental to biodiversity.Each and every single one of the discussed subsidies has its own goals and purposes.(1) Cross compliance, (2) agro-environmental measures, (3) less favoured area payments and(4) subsidies for organic farming have different objectives, which will be addressed in thispaper. I will aim at analysing their overall contributions to the goal of fostering sustainablefarming within the EU, through highlighting the benefits, strengths and contributions of thesefour types of subsidies.This paper will examine their key contents and provisions, their current level ofimplementation and practical measures that could be put in place to further enhance theirsuccessful implementation.